2002
DOI: 10.1111/j.1574-6941.2002.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and activity of the bacterial community in the rhizosphere of different plant species and the effect of arbuscular mycorrhizal colonisation

Abstract: The aim of this study was to determine if arbuscular mycorrhizal (AM) colonisation influences rhizosphere bacteria differently depending on plant species. Thus, the effect of AM colonisation (Glomus intraradices) on rhizosphere bacteria of subterranean clover, cucumber, leek and maize was studied. The bacterial activity was measured as thymidine or leucine incorporation and bacterial numbers as colony forming units and acridine orange direct counts. The phospholipid fatty acid (PLFA) pattern was used to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…Furthermore, the most predominant bacterial families in the roots of reed and Japanese loosestrife were different; Burkholderiales genera incertae sedis for reed (15%) and Sinobacteraceae for Japanese loosestrife (12%). It has been reported that the bacterial community inhabiting the roots of terrestrial plants such as annual plants and trees apparently varies among different species (10, 11, 35, 36, 49). Therefore, the findings shown above suggested that aquatic plants might also harbor species-specific bacterial communities on the roots as is the case for terrestrial plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the most predominant bacterial families in the roots of reed and Japanese loosestrife were different; Burkholderiales genera incertae sedis for reed (15%) and Sinobacteraceae for Japanese loosestrife (12%). It has been reported that the bacterial community inhabiting the roots of terrestrial plants such as annual plants and trees apparently varies among different species (10, 11, 35, 36, 49). Therefore, the findings shown above suggested that aquatic plants might also harbor species-specific bacterial communities on the roots as is the case for terrestrial plants.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies of the microbial communities associated with the roots of terrestrial plants have so far been reported (8, 10, 11, 18, 24, 32, 35, 36, 49), suggesting that the microbes might exert a beneficial, neutral or deleterious influence on plant growth. Some of these studies also revealed that the roots of different plant species interacted with different microbial communities (10, 11, 35, 36, 49), and that the growth and activity of microbial populations in the area, which is adjacent to the root system (rhizosphere) and on the external surface of the roots (rhizoplane) are, in general, greater than that root-free soil due to root exudates such as amino acids, sugars and growth factors (11, 26, 36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They can form living root-soil links and a specific zone of soil, which is called mycorrhizosphere [2]. The AM fungi can have an effect on rhizosphere through various mechanisms, such as alterations in soil properties, microbial community, and/or root exudates [35]. The symbiosis may help plants to thrive by colonizing a wide soil volume, accelerating photosynthesis, protecting plants against plant pathogens and pests in soil, absorbing resources efficiently, and dissipating of pollutants from the soil [4, 68].…”
Section: Introductionmentioning
confidence: 99%
“…Wieland et al (2001) reported that the type of plant species (clover, bean, or alfalfa) selects for the microbial communities on their roots. Plant species are known to produce specific exudates (Söderberg et al, 2002), different leaching metabolites and proportions of chemicals (Fiehn et al, 2000) which can impact the bacterial community structure. These findings support previous results in our laboratory in which the epiphytic bacterial community structure of Hydrilla was found to be distinct from that on the native plant species eelgrass (Gordon-Bradley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%